Public health implications of bacterial and fungal bioaerosol concentrations in outdoor air - Somayyeh Ziaei; Maryam Sarkhosh; Mahdi Saeidi; MohammadMahdi Sarkhoshkalat (Scientific Reports)
Abstract Exposure to bioaerosols has been associated with various health issues, including infectious diseases, acute toxicity, allergies, and cancer. This study aimed to assess the concentrations of bacterial and fungal bioaerosols in Mashhad, Iran, and examine their correlation with PM2.5 levels in outdoor air. Bioaerosol samples were collected at six locations using active sampling techniques. The concentration of airborne bacteria ranged from 36.66 to 89.49 CFU/m³, while fungal concentrations varied between 52.31 and 102.59 CFU/m³. The most frequently identified bacterial species were Staphylococcus epidermidis and Escherichia coli, whereas Aspergillus and Penicillium species were the dominant fungi. A strong positive correlation was observed between bacterial aerosol concentrations and PM2.5 levels, while airborne fungal concentrations exhibited a moderate positive correlation with PM2.5. The strong association between bacterial bioaerosols and PM2.5 suggests that increased bacterial levels are linked to higher dust concentrations, a pattern consistent with findings from other dust-prone regions worldwide. The HQ values of bioaerosols in six sampling sites were all lower than 1. However, the association between higher bioaerosol concentrations and elevated PM2.5 levels suggests possible interactions between microbial aerosols and air pollutants. This study underscores the importance of continuous bioaerosol monitoring to mitigate public health risks, particularly in densely populated urban areas where exposure is more pronounced. Additionally, bioaerosols play a role in the natural cycling of biological materials.